1985
DOI: 10.1002/mus.880080111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation in Duchenne Dystrophy: V. Use of creatine kinase and pyruvate kinase in carrier detection

Abstract: We have determined the value of creatine and pyruvate kinase (CK and PK) in carrier detection by evaluating 811 females in 73 families participating in the Collaborative Investigation of Duchenne Dystrophy. Thirty-nine obligate carriers, 244 normal controls (paternal females), as well as 76 possible carriers and 351 carrier suspects had three CK and PK specimens analyzed at a central laboratory. The CK and PK values varied with age in normals: both fell with age early in life, and CK rose after the fifth decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 32 publications
(1 reference statement)
1
14
0
Order By: Relevance
“…Earlier studies on serum CK and PK levels from possible younger carriers suggest that enzyme activities are higher during childhood and early adolescence than in adulthood [Zatz et al, 1976;Ni cholson et al, 1979;Percy et al, 1979;Lane and Roses, 1981;Griggs et al, 1985]. The latter authors further suggested that among obligate carriers PK is more agedependent than CK.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Earlier studies on serum CK and PK levels from possible younger carriers suggest that enzyme activities are higher during childhood and early adolescence than in adulthood [Zatz et al, 1976;Ni cholson et al, 1979;Percy et al, 1979;Lane and Roses, 1981;Griggs et al, 1985]. The latter authors further suggested that among obligate carriers PK is more agedependent than CK.…”
Section: Discussionmentioning
confidence: 74%
“…Lange and Zatz [1979] found for the group of DMD carriers a linear regres sion that could explain the age-related de crease in serum CK levels. However, no significant decrease in serum CK activity was detected in a follow-up study of 16 possible and obligate adult carriers , A decrease in serum PK levels with age in DMD carriers has been suggested by Percy et al [1979] and Griggs et al [1985]. The latter authors also reported a lower detection rate among obligate carriers than in their daughters using both CK and PK determinations.…”
Section: Introductionmentioning
confidence: 82%
“…The highest estimated hcritabilities were also observed among females unlikely to be heterozygotes for the abnormal gene (ta ble 3). The most likely explanation for such findings is that in these groups the majority of females arc probably noncarri ers of the defective gene, and therefore their serum enzyme levels follow the multifactorial pattern of inheritance observed for normal individuals [34][35][36], Probably the same effect would be expected among obligate carriers (mothers and daughters) with normal enzymes, but the sample is not large enough to test such hypothesis.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, investigations in normal individuals have also shown a sta tistically significant intrafamilial correla tion for both serum CK and PK [34][35][36], Estimates of the heritability of serum CK and PK in normal individuals suggest a multifactorial inheritance. In a study of normal female twins, Whitfield and Mar tin [34] estimated a heritability of 0.81 for CK, while Rapaport et al [36], in a large sample of monozygotic and dizygotic twins of both sexes, estimated a heritability of 0.55 for CK, 0.66 for PK and 0.49 for CK in female twins.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult Brazilian female population, height can be estimated by dividing the wingspan by 1.03 [18]. A severe manifestation of DMD is uncommon in women, with mild to moderate muscular weakness only being expected and increased creatine kinase (CK) and creatine kinase isoform MB levels (CKMB) [19]. In case 1 in particular, the concentration of CK and CKMB was reduced due to severe muscle atrophy (175 U/L and 16 U/L, respectively).…”
Section: Discussionmentioning
confidence: 99%